Urban Expansion and Its Impact on Green Spaces of Dehradun City, Uttarakhand, India - Gupta, Peeyush; Goyal, Swati (International Journal of Environment, 2014)
Urbanization is on increase because of heavy population pressure, industrialization, and better job opportunities in plane areas compared to Himalayan terrain. The urbanization has also added hypertension because of very fast life and lack of recreational opportunities within easily accessible distances. Deforestation is the permanent destruction of indigenous forests and woodlands. The term does not include the removal of industrial forests such as plantations of gums or pines. Deforestation is clearing of forests on a massive scale, often resulting in damage to the quality of the land. Urbanization is one of the major causes of the deforestation. Urban green space planning is an important component of urban ecosystems; provide many environmental and social services that contribute quality of life in the cities.The green spaces are said to be the lungs of the urban ecosystem. The process of urbanization led to natural landscape change. In the process tree cover, green spaces and wetlands were recklessly converted into built-up areas in the past and the process is still going on. Due to availability of required infrastructure, Dehradun was named interim capital of the nascent Himalayan state of Uttarakhand in 2000. Other regions of Uttarakhand is also experiencing rapid urbanization. The hill districts adjoining Dehradun district have witnessed a four-fold increase in the number of towns between 1901 and 2001. The population of Dehradun registered increase of 41.08 % between1961-1971, 32.84 % between 1971-81, 25.39 % between 1981-91 and during 1991-2001 it increased by 52.45 %. The temporal imaging of remote sensing data and socio-economic data of 1982 will be used for overall spatial monitoring. DOI: http://dx.doi.org/10.3126/ije.v3i4.11731 International Journal of Environment Volume-3, Issue-4, Sep-Nov 2014 Page: 57-73